Pengaruh Ketepatan Sasaran Anggaran dan Pengendalian Manajerial Sektor Publik terhadap Akuntabilitas Kinerja pada Dinas Kesehatan Provinsi Kalimantan Barat - Markus, Markus (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines the effects of budget target accuracy and public-sector managerial control on performance accountability at the West Kalimantan Provincial Health Office. The study employs a quantitative approach using primary data collected through questionnaires. The sample was selected through purposive sampling and consisted of 57 respondents. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS version 25. The results show that budget target accuracy has a positive and significant effect on performance accountability, while managerial control also has a positive and significant effect. Simultaneously, budget target accuracy and managerial control significantly affect performance accountability. The coefficient of determination is 64.5%, indicating that the two independent variables explain 64.5% of the variation in performance accountability, while the remaining 35.5% is explained by other factors outside the research model.